Implantación de un sistema contable en la tienda Reina del Cisne de la ciudad de Loja, periodo abril a junio 2016 - Chamba Tigre, Mayra Patricia (2017)
The thesis titledg "IMPLEMENTATION OF AN ACCOUNTING SYSTEM TO THE QUEEN STORE OF THE SHOP CITY OF PERIODO APRIL TO JUNE 2016" was developed based on the general objective, which allowed to obtain true, real and timely information of the activities Which are being carried out in it, in order to know the economic and financial situation of the same for the correct decision-making of its owner. To meet the specific objectives; The inventory was started the same that was done by means of the physical verification of the goods, rights and obligations, in addition the cash register was elaborated to know the exact amount of monetary resources that it has when starting its activities and with this information The initial inventory was carried out; The Plan and Accounts Manual was prepared in accordance with the needs of the business, the Chart of Accounts was structured based on the accounts used for this type of company and in accordance with current accounting standards and principles; The accounts manual describes each of the accounts, their dynamics and their balance with the purpose of facilitating the recording of the operations that are generated daily; The control and registration of the merchandise account was carried out through the multiple account system in order to know the movement of this account during the 5 accounting process, and finally the accounting process was developed from the initial situation to the presentation of the States Financial Services With the implantation of the accounting system in the Reina del Cisne Store, it was possible to show that it has a usefulness; The same that can be increased if proper control is applied to the merchandise account, accounts receivable and accounts payable; Which will allow the owner to optimize their resources and promote the operational efficiency that contribute to the development of their business. Finally, the most relevant conclusions and recommendations of thesis work are described, such as: That the implementation of an accounting system was carried out in the Loja Reina del Cisne in the city of Loja, allowing real and timely knowledge of the economic situation of the company; And the owner is encouraged to accept this accounting system; Since it was prepared according to the needs of the business and in accordance with generally accepted accounting principles and current accounting standars